Drosophila parabss Flies as a Screening Model for Traditional Medicine: Anticonvulsant Effects of Annona senegalensis - Dare, Samuel S.; Merlo, Emiliano; Rodriguez Curt, Jesus; Ekanem, Peter E.; Hu, Nan; Berni, Jimena (Frontiers in Neurology, 2021)
Epilepsy is among the most common serious neurological disorders and affects around 50 million people worldwide, 80% of which live in developing countries. Despite the introduction of several new Anti-Epileptic Drugs (AEDs) in the last two decades, one third of treated patients have seizures refractory to pharmacotherapy. This highlights the need to develop new treatments with drugs targeting alternative seizure-induction mechanisms. Traditional medicine (TM) is used for the treatment of epilepsy in many developing countries and could constitute an affordable and accessible alternative to AEDs, but a lack of pre-clinical and clinical testing has so far prevented its wider acceptance worldwide. In this study we used Drosophila melanogaster paralyticbangsensitive(parabss) mutants as a model for epileptic seizure screening and tested, for the first time, the anti-seizure effect of a non-commercial AED. We evaluated the effect of the African custard-apple, Annona senegalensis, which is commonly used as a TM for the treatment of epilepsy in rural Africa, and compared it with the classical AED phenytoin. Our results showed that a stem bark extract from A. senegalensis was significantly more effective than a leaf extract and similar to phenytoin in the prevention and control of seizure-like behavior. These results support that Drosophila constitutes a robust animal model for the screening of TM with potential value for the treatment of intractable epilepsy.